Research on the Path of Improving the Classroom Management Ability of Primary School Mathematics Teachers - Yuan, Li (Pacific International Journal, 2026)
In classroom teaching, teachers serve not only as knowledge transmitters but also as designers, organizers, and managers of instructional activities. Effective classroom management is a critical factor in ensuring educational quality. This study investigates the shortcomings in classroom management practices among primary school mathematics teachers in Hohhot by analyzing extensive literature and survey data. The research focuses on five key aspects: classroom discipline management, time management, student engagement, physical environment, and classroom atmosphere. Based on these findings, three actionable strategies are proposed to enhance classroom management capabilities: subject management, time management, and student activity management. The study aims to provide theoretical guidance for primary school mathematics teachers to improve classroom management, thereby effectively stimulating students’ learning motivation and promoting academic achievement. This research holds significant practical value for frontline mathematics educators and serves as a valuable reference for school administrators seeking to optimize classroom environments.